A Study on the Extent of Resistance to Change on Business Transformation Initiatives in Pos Malaysia - Mohd Yusri, Dolah (2011)
Many organizations, including Pos Malaysia Berhad embarked in business transformation initiatives to enhance capabilities, improve performance and provide competitive advantage for business. In implementing business transformation initiatives, one of the issues that need to be addressed is the resistance to change. Many implementations have failed due to strong resistance from the employees. Thus, the purpose of this study is to test the impact of resistance to change on transformation initiatives' implementation success and how change management initiatives act in the capacity as a moderator. There were 130 copies of questionnaires were distributed to Pos Malaysia employees but only 124 feedbacks received from respondents that used as a study population sample. Analysis methods used to examine the relationship among variables in this study were frequency analysis, reliability analysis, correlation analysis, factor analysis and hierarchical regression analysis. Based on hierarchical regression analysis, the finding of this study revealed that resistance to change is negatively related with achievement of predetermined goals and user satisfaction. Further, change management initiatives were found did not act as a moderator for both relationships. This study concludes that the human factor is important in business transformation initiatives' success.